2020
DOI: 10.1016/j.immuni.2019.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Immune Sensing of Cell Death through Recognition of Histone Sequences by C-Type Lectin-Receptor-2d Causes Inflammation and Tissue Injury

Abstract: The immune system monitors the health of cells and is stimulated by necrosis. Here we examined the receptors and ligands driving this response. In a targeted screen of C-type lectin receptors, a Clec2d reporter responded to lysates from necrotic cells. Biochemical purification identified histones, both free and bound to nucleosomes or neutrophil extracellular traps, as Clec2d ligands. Clec2d recognized poly-basic sequences in histone tails and this recognition was sensitive to post-translational modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 81 publications
3
69
0
3
Order By: Relevance
“…In fact, this mechanism driven by HMGB1 has been proposed to play a role in the severe pulmonary inflammation occurring at late stages of COVID-19 [ 55 ]. In a similar way, histones released upon cell death are recognized by the CLR CLEC2D, transferring them to endosomal compartments where histones-bound DNA triggers TLR9-mediated inflammatory responses [ 56 •• ].…”
Section: Inflammatory Sensing Of Tissue Damagementioning
confidence: 99%
“…In fact, this mechanism driven by HMGB1 has been proposed to play a role in the severe pulmonary inflammation occurring at late stages of COVID-19 [ 55 ]. In a similar way, histones released upon cell death are recognized by the CLR CLEC2D, transferring them to endosomal compartments where histones-bound DNA triggers TLR9-mediated inflammatory responses [ 56 •• ].…”
Section: Inflammatory Sensing Of Tissue Damagementioning
confidence: 99%
“…Only a handful of empirical studies have reported on the mechanisms of NET removal. In the majority of them, the process was studied in vitro / ex vivo on isolated cells ( Supplementary Table S1 and Figure 3 ) [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Regrettably, only a couple of papers presented in vivo data [ 35 , 62 ].…”
Section: On How Nets Are Removedmentioning
confidence: 99%
“…What is more, proteomic analyses of NETs formed in response to PMA identified higher content of histone H2A and histone H3.1, whereas histone one family protein concentrations (H1.0, H1.4, and H1.5) are significantly higher in A23187-induced NETs [ 107 ]. In fact, two very recent publications report on a critical role of the histone component of NETs in their recognition as well as on involved receptors [ 81 , 82 ], issues discussed in the following paragraph.…”
Section: On How Nets Are Removedmentioning
confidence: 99%
See 2 more Smart Citations